The Application of SWOT Analysis in Determining Competitive Strategy at CV. Dichandra Labglass - Nuniek Dewi Pramanik; Jusuf Nurdin; Adi Chandra Triana (CV Edujavare Publishing, 2026)
This research aims to formulate an appropriate competitive strategy for CV. Dichandra Labglass in facing competition within the laboratory glassware manufacturing industry. The method employed is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to map the company's internal and external factors. The results indicate that CV. Dichandra Labglass is positioned in an aggressive growth quadrant (Growth Oriented Strategy). The company's primary strengths lie in high-quality borosilicate materials, glassblowing artisans with over 15 years of experience, and a credible digital reputation as a Star Seller. However, the company faces internal constraints such as semi-manual production technology, a shortage of skilled labor due to the absence of formal education, and non-integrated administrative management. Externally, government policies regarding Domestic Component Level (TKDN) and industrial downstreaming trends present significant opportunities, amidst threats from cheap imported products and exchange rate volatility. The resulting competitive strategy is a differentiation strategy focused on after-sales services, including repair guarantees and specific product customization. This study concludes that strengthening brand identity and optimizing the digital ecosystem are keys to the company's sustainability in both domestic and international markets.